2021
DOI: 10.1111/iep.12392
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between aryl hydrocarbon receptor and IL‐17+ and Foxp3+ T‐cell infiltration in bladder cancer

Abstract: Bladder cancer (BC) is one of the most prevalent cancers around the world and, if not treated well, has high morbidity and mortality. Many studies have indicated that there may be various roles for the aryl hydrocarbon receptor (AHR) in the immune system. The aim of this study was to determine the frequency of Foxp3+ regulatory T (Treg) and T helper 17 cells (Th17) in BC tissue in comparison with controls and determine the relationship between AHR, Foxp3+ Treg and Th17 cells in BC. A total of 40 patients with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…According to earlier studies, Tregs inhibit long-lasting immune reactions to viruses, tumors, and self-antigens; the infiltrate tumor tissue and are linked to a bad prognosis in cancer patients; the quantity of Treg was negatively correlated with recurrence-free survival in BUC and substantially increased in peripheral blood and tumor tissue[ 7 ]. The grade and stage of BUC were significantly associated with the proportion of Foxp3+ Tregs[ 8 ]. The most significant component of natural immunity is played by NK cells, which can directly destroy target cells like cancerous or virus-infected ones.…”
Section: Resultsmentioning
confidence: 99%
“…According to earlier studies, Tregs inhibit long-lasting immune reactions to viruses, tumors, and self-antigens; the infiltrate tumor tissue and are linked to a bad prognosis in cancer patients; the quantity of Treg was negatively correlated with recurrence-free survival in BUC and substantially increased in peripheral blood and tumor tissue[ 7 ]. The grade and stage of BUC were significantly associated with the proportion of Foxp3+ Tregs[ 8 ]. The most significant component of natural immunity is played by NK cells, which can directly destroy target cells like cancerous or virus-infected ones.…”
Section: Resultsmentioning
confidence: 99%
“…It is made up of the Per‐Arnt‐Sim structure, which associates with a variety of both exogenous and endogenous compounds as well as certain cofactors such as heat shock protein 90 (HSP90) and proteins associated with HBV‐X 43,48 . AhR is essential for mediating the biological response to a range of physiological and environmental chemicals 43,49 . AhR is present in intrinsic and specific immune cells and regulates immune cell proliferation, differentiation and cytokine production, which are important for infection and inflammation control 50,51 …”
Section: Discussionmentioning
confidence: 99%
“…43,48 AhR is essential for mediating the biological response to a range of physiological and environmental chemicals. 43,49 AhR is present in intrinsic and specific immune cells and regulates immune cell proliferation, differentiation and cytokine production, which are important for infection and inflammation control. 50,51 Recently, it has been discovered that AhR plays an important role in controlling Th17/Treg equilibrium.…”
Section: Discussionmentioning
confidence: 99%
“…FoxP3 is a transcription factor required by regulatory T cells (Tregs) to maintain immune cell homeostasis and inhibit antitumor immune responses [24]. Although FoxP3 + TILs were shown to predict better survival in head and neck, bladder, and colon cancers [20,25,26], numerous studies suggested that Tregs are immunosuppressive and that their presence/abundance is associated with poor prognosis in patients with cancer [21,27,28]. However, some studies reported TILs as a prognostic marker in bladder cancer [21,22].…”
Section: Discussionmentioning
confidence: 99%